THE HISTORY OF PEDAGOGY AS A TEACHING SUBJECT (Web of Teachers: Inderscience Research, 2023)
This article aims to examine the evolution of pedagogy as a distinct field of study, exploring its various philosophical underpinnings and influential educators throughout history. By understanding the origins and development of pedagogy, we can gain insights into contemporary educational practices and their effectiveness in promoting effective learning. The importance of studying the history of pedagogy highlights the significant role it plays in shaping current educational practices. Understanding the evolution of pedagogical approaches provides educators with a deeper insight into the foundations of teaching and learning. It allows them to critically evaluate existing methodologies and make informed decisions about instructional strategies to improve student outcomes.